Entrepreneurship And Luck As Source - Based Study On Small And Medium Enterprise In Malaysia - Ong, Jeen Wei (2008)
This study focuses on entrepreneurial traits, entrepreneur's human capital, and Information Technlogy competence to study the competitive advantage in small and medium enterprise. In addition, many established firms today achieve their success due to some extent of luck.